Integrative in silico and in vitro analysis of Pinus roxburghii essential oil: unveiling its antioxidant, antidiabetic, and antiglycation potential - Naz Qaisrani, Rubina; Iram Niaz, Shah; Bano, Raheela; Abuelizz, Hatem A.; Alvi, Arooj Mohsin; Chaman, Sadia; Aziz, Qaiser; Wazir, Muhammad Asif; Akram, Muhammad; Ishtiaq, Saiqa; Ramzan, Muhammad; Amin, Adnan (Frontiers in Pharmacology, 2025)
IntroductionEssential Oils (EOs) are a rich source of secondary metabolites that exhibit various biological activities.MethodsThis study includes GCMS analysis of Pinus roxburghii EO, computational investigation including drug likeness, ADMET properties, molecular docking, and in vitro evaluations for possible antioxidant, antidiabetic, and anti‐AGEs actions.ResultsGCMS analysis identified β‐pinene (30%) as major component, succeeded by caryophyllene (29.37%), o‐xylene (8.98%), aromadendrine (8.29%), and α‐himachalene (6.82%). Molecular docking showed significant interaction of transcription regulators 1JIJ with Caryophyllene oxide (ΔG ‐7.5 (kJ mol‐1), 3TOP with α‐himachalene (ΔG ‐6.8 (kJ mol‐1) and 4F5S with α‐himachalene (ΔG ‐7.7 (kJ mol‐1). The EO exhibited elevated phenolic content (26.3±0.45 mg/G GAE) and considerable antioxidant capacity in DPPH (14.2±0.62), H2O2 (73.3±1.7), and FRAP assays (312±14.6 μg). The antidiabetic assays demonstrated a notable inhibition of α‐glucosidase (IC50 0.12 mg/mL) and advanced glycation end products (AGEs) in both non‐oxidative (IC50 0.052 mg/mL) and oxidative modes (IC50 1.61 mg/mL). During mechanistic investigations it was observed that EO exerts a protective effect against β‐amyloid formation and significantly entraps carbonyl moieties.Conclusions It was observed that P. roxburghii EO has notable antidiabetic and anti-AGEs properties and these finding support a good potential for management of diabetes and allied co-morbidities. In future formulation design studies can be helpful for pharmaceutical industry to opt the formulation.